Adjacency Pairs as Influenced by Gender: a Case of Casual Conversation in the Public Figure - Jati Widya Iswara (Universitas PGRI Semarang, 2019)
This research aims at revealing in analyzing of adjacency pairs in conversation of public figure which influenced by gender. The participants were Bripda Litta Rahmawati as a SUBBIDPROVID BIDPROPAN POLDA JATENG POLDA JATENG, Jati Widya Iswara as an English teacher and founder of minimalist library, and the host Avied Satrio Jati. The data taken from transcript of dialogue of conversation. The topic of conversation was about the history of life of both guest start. Since it was described by words to show the result and it is very possible to use qualitative method. The objectives of this research are to find out how can gender influenced adjacency pairs in the conversation. In the end of the research, the researcher found some of adjacency which spoke and influenced of gender. Both of the guests star and the host shown the different in producing adjacency pair because some effect of gender and the occasion.